ANALYSIS OF THE INFLUENCE OF PRICE AND SERVICE QUALITY ON CUSTOMER SATISFACTION IN BISMILLAH AUDIO SOUND SYSTEMS - Haryono, Achmad Fawaid; Mujiyanti, Sri Ayudha; Azizah, Nur (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to analyze the influence of price and service quality on customer satisfaction in the sound system rental business of Bismillah Audio in Situbondo Regency. The method used in this study is a quantitative approach with an associative causal research design. Data collection was conducted through a questionnaire distributed to 50 respondents consisting of Bismillah Audio service users. The research instruments were tested for validity and reliability, indicating that all questionnaire items were valid and reliable. Data analysis techniques included multiple linear regression, t-test (partial), F-test (simultaneous), and the coefficient of determination (R²). The results of the study indicate that the service quality variable has a positive and significant effect on customer satisfaction, with a regression coefficient value of 0.398 and significance of 0.000 (< 0.05). Conversely, the price variable does not show a significant effect on customer satisfaction partially, with a significance value of 0.310 (> 0.05). However, simultaneously, price and service quality have a significant effect on customer satisfaction with a coefficient of determination (R²) of 0.949. This indicates that 94.9% of the variation in customer satisfaction can be explained by these two independent variables, while the rest is influenced by other factors outside the model.